IMPLEMENTASI PAYMENT REMINDER PADA RANCANG BANGUN SISTEM PEMBIAYAAN SEKOLAH DI PAUD TERPADU AISYIYAH 1 BANGIL BERBASIS WEB MENGGUNAKAN FRAMEWORK LARAVEL - Fitriya, Nuril; Alimin, Alimin* (LPPM ITB Yadika Pasuruan, 2024)
Abstract : Aisyiyah 1 bangil integrated preschool is one of the integrated early childhood schools in bangil, pasuruan district. processing school fee payments is still implemented manually until now, namely still using ledgers, making work ineffective and inefficient. often parents / guardians of students are also late in making payments and teachers also cannot remind parents / guardians of their students one by one. from this problem, the idea emerged to make a school financing application by implementing a payment reminder in which you can manage payment data and provide information to student guardians regarding tuition fees. the methodology used in making this application is the waterfall method. the programming language used is php and the laravel framework, the database uses mysql and gammu as a tool for connecting sms gateway. supported by the existence of a computer at the institution. with the application of the school financing system, it is hoped that it will make it easier for financial officers to manage payment and provide information to parents of students